Analysis Factors Affecting Customer Loyalty of Indihome Provider During The Covid-19 Pandemic In Surakarta - Aini Dwi Mutikasari; Ihwan Susila (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this study is to investigate how customers feel about IndiHome's service quality, brand perception, and trust in light of the current Covid-19 outbreak in Surakarta. Participants were people who used the IndiHome service in the Surakarta region. For this study, we employed a sampling strategy that was both statistically and practically effective. In Surakarta, where IndiHome is popular, an online questionnaire was administered to 164 customers. For the quantitative study, we used SPSS version 25's multiple regression function. According to the results, trust plays a significantly lower role in determining customer loyalty than do service quality and brand image. This paper gives scholars and businesspeople in Surakarta insights on the loyalty of IndiHome customers to their service provider.